Development of novel fibre reinforcement architectures - Karanatsis, Dimitrios (2020)
This research focuses on the development of novel carbon fibre reinforcements and the effect of the support structure on the physical properties of the produced fabric. Scrim is the selected support structure for the focus of this work. The scrim is the support structure for the carbon fibres and it is used for the manufacture of non-crimp fabrics (NCFs). The scrim is an open mesh grid construction comprising of individual threads and can be placed at different orientations. The carbon fibre tows are bonded onto the substrate by means of pressure and heat. The manufactured fabric can potentially improve the physical and mechanical properties of a fibre-reinforced composite component when compared with a conventional stitched fabric, as it does not interfere to a large degree with the fibre arrangement and alignment. By systematically varying different parameters of the scrim, the effect on the physical properties of the fabrics was examined. The selection of an appropriate non-crimp fabric for a specific application requires an extensive knowledge and a deep understanding of all the process parameters involved during composite manufacture. This selection is a complex process as it requires a high number of different adjustable factors in manufacturing that can affect a structural fabric’s behaviour during processing. Knowing the exact relation between the manufacturing parameters and the processing parameters will lead to improved methods and reduced manufacturing time, cost and even weight of the composite components. The goal of this study is to understand how the support structure in newly developed non-crimp fabrics affects the manufacturing process of carbon fibre composite materials. Moreover, a newly developed automated dry fibre placement process was developed which utilizes the newly developed substrates and non-crimps fabrics manufacture. Net shape manufacture is presented as an important cost reduction step in the evolution of composite materials within the automotive industry, particularly as their use extends from low to high volume applications. The new process aims to minimize waste associated with the production of composites as well as improve the performance of the manufactured composite parts. Experimental observations show that the in-plane permeability of the scrimbacked fabrics is affected by the scrim architecture. As the permeability of unidirectional carbon fibre bundles is inherently high parallel to the fibre direction and low in the transverse direction, when a scrim is added, flow is locally enhanced parallel to the fibre bundles, since the geometry of flow channels formed in the fabric is affected. In particular, new flow channels can form along transverse scrims threads which can increase the transverse bundle permeability. Moreover, experimental observations show that shear behaviour of the fabrics is not affected to a high degree on biaxial scrim supported fabrics. Formability of the fabrics remains almost the same for every scrim architecture and this can lead to further weight savings as the additional scrim yarns do not contribute to a significant degree to the processing characteristics of the fabrics. A secondary study, before discussing the development of the new materials, was focused on modifying existing NCF products and examining their physical properties in order to understand the significance of the support structure on the processing of NCFs. Although there is a significant amount of research focused on examining the effect of the stitch thread of non-crimp fabrics, the number of studies using bespoke materials is limited as samples are only available from specific and widely used materials. The cost of ordering for example materials with specific stitch thread lengths would be prohibitive due to the fabric manufacturer requiring minimum orders that would exceed a typical research budget. The need to explore a systematic approach on changing the stitch thread parameters, and more specifically for this study the stitch thread tension, on NCFs was important for the development of the new structural fabrics. As the author had access to the manufacturing equipment at Hexcel Leicester, he could systematically change parameters in the NCFs, designing and manufacturing specific materials. Moreover, the stitch thread parameters were strictly controlled during the production stages, in order to be confident that the results would reflect changes in the support structure. Constraining the bundle mobility by increasing the stitch tension was found to result in decreasing levels of fibre bundle waviness. The stitch thread tension affects the size and geometry of fibre bundles and inter-bundle gaps in the fabric. Experimental observations suggest that this has an effect on the in-plane permeability, particularly transverse to the fibre bundles. Variations of the stitch thread tension will translate into rearrangements in the fibre structure and thus affect the permeability of the reinforcement. The higher the stitch tension, the tighter and closer packed the arrangement of the fibre filaments that can lead into alterations of the flow during liquid resin injection for composite manufacture. Moreover, experimental observations show that shear behaviour of the fabrics is affect by the stitch tension and there is a linear effect to the degree of shear they experience. High stitch tension results in reduced formability of the fabric on a complex geometry. As the stitch thread rearranges the fibre filaments, these are packed in a tight formation where the bundles tend to have constricted movement.